E-Commerce, Customer Relationship Management and Artificial Intelligent amid COVID-19 - Ifta Firdausa Nuzula; Mohammad Allatas Muryanto; Vo Hung Cuong (The Indonesian Institute of Science and Technology Research, 2022)
Coronavirus is intensely changing various aspects of life, including in business. The pandemic has altered a variety of customer behaviours. The ability of companies to understand these behaviour changes affects business continuity. This study explains the relationship between customer relationship management (CRM) and e-commerce and its trends during the pandemic. This research is descriptive qualitative research using secondary data. This study found that CRM and e-commerce issues grew rapidly during the pandemic. These results show that customer awareness of e-commerce is increasing to make transactions of their needs. Simultaneously, this customer behaviour is anticipated by business people by improving CRM as an effort to manage customer satisfaction. Some results in different countries are not always the same response between CRM and e-commerce.